The shaping of gut immunity in cirrhosis - Muñoz, Leticia; Caparrós, Esther; Albillos, Agustín; Francés, Rubén (Frontiers in Immunology, 2023)
The liver and the brain are connected to the gut through different metabolites that enable their bidirectional crosstalk impacting their function. This gut-liver-brain axis is altered in cirrhosis, contributing to the progress of disease and the development of clinically relevant complications. The altered bile acids metabolism in the cirrhotic liver and the increase in the blood-brain barrier permeability, along with the progressive dysbiosis of intestinal microbiota, contribute to gut barrier dysfunction, altered at both physical and immunological layers. The structural changes at the epithelial and gut vascular barriers, and the compromised antimicrobial host defense shape a pro- inflammatory environment that activates different T and B cell responses, further disrupting gut barrier integrity. Several therapeutic approaches targeting the intestinal homeostasis in cirrhosis, mainly focused on the interactions between the altered microbiota and the gut immune system such as probiotics, fecal microbiota transplantation or farnesoid X receptor agonists, among others, are also discussed.